2022
DOI: 10.3390/cancers14225643
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Clinical Evidence Supports a Key Role for Cell Division Cycle Associated 5 (CDCA5) as an Independent Predictor of Outcome in Invasive Breast Cancer

Abstract: Background: Cell Division Cycle Associated 5 (CDCA5) plays a role in the phosphoinositide 3-kinase (PI3K)/AKT/mTOR signalling pathway involving cell division, cancer cell migration and apoptosis. This study aims to assess the prognostic and biological value of CDCA5 in breast cancer (BC). Methods: The biological and prognostic value of CDCA5 were evaluated at mRNA (n = 5109) and protein levels (n = 614) utilizing multiple well-characterized early stage BC cohorts. The effects of CDCA5 knockdown (KD) on multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…We next investigated the potential mechanisms of CDCA5-mediated ccRCC progression. The activation of CDCA5 has been reported to induce breast tumor progression via PI3K-AKT-mTOR signaling pathway [ 12 , 16 ]. As well-characterized PI3K-AKT-mTOR effectors, the phosphorylation and activation of AKT, 4E-BP1 and S6 regulates cell survival, proliferation, and growth [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated the potential mechanisms of CDCA5-mediated ccRCC progression. The activation of CDCA5 has been reported to induce breast tumor progression via PI3K-AKT-mTOR signaling pathway [ 12 , 16 ]. As well-characterized PI3K-AKT-mTOR effectors, the phosphorylation and activation of AKT, 4E-BP1 and S6 regulates cell survival, proliferation, and growth [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…CDCA5 regulates sister chromatid cohesion and plays essential roles in mitosis [ 7 ]. CDCA5 expression is associated with poor prognosis in several cancers [ [10] , [11] , [12] , [13] ]. CDCA5 has been reported to be associated with cell proliferation, apoptosis, and cell cycle arrest; however, its relevance to the immune microenvironment has not been well studied [ 7 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have reported that CDCA5 may play a role in cancer progression. High levels of CDCA5 are associated with worse outcomes in patients with cancers, such as lung [ 10 ], breast [ 11 ], gastric [ 12 ] and prostate cancers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%